Strategi Penerapan Kurikulum Merdeka di SMAN 2 Ponorogo - Andreas Fredyansa Harwisaputra; Anggi Nur Eka Safitri; Anggi Wahyuning Utami; Anik Sudarsih; Mambaul Ngadhimah (Southeast Asian Journal of Islamic Education Management, 2023)
Along with the times, especially in the education sector, innovation is needed according to relevant needs. In an effort to achieve this, the way that can be taken is by updating the relevant curriculum. With the curriculum transformation, it is hoped that it can improve the quality of education. One of the curricula recommended by the government is the Merdeka Curriculum. In achieving maximum results in its implementation, an effective strategy is needed. For this reason, this article aims to explore the strategy for implementing the Merdeka Curriculum carried out by SMAN 2 Ponorogo. In this study using descriptive qualitative methods with data collection techniques interviews and observations and data analysis using miles and Huberman and or other relevant methods. The results of this study in the implementation strategy of SMAN 2 Ponorogo carried out activities in the form of IHT (In House training) on the Independent Curriculum. In its implementation, there are still various obstacles ranging from the lack of teacher knowledge about the independent curriculum, lack of socialization and paradigm shifts. Based on the findings, it can be concluded that effective strategies have been implemented to overcome the challenges of implementing the independent curriculum at SMAN 2 Ponorogo. This article provides recommendations for other schools that will implement the independent curriculum to organize intensive training activities for teachers and the formation of a curriculum support team.